PENGERITINGAN RAMBUT BERGANDA (DOUBLE PERMING) DALAM TATA RIAS: STUDI DESKRIPTIF KUALITATIF BERBASIS STUDI PUSTAKA - Isnaini, Nadya; Sahira, Jehan; Syahpitri, Mutiara; Rezki Fauzani, Asrah; Putri, Mutia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Hair perming is one of the techniques in cosmetology aimed at transforming the structure of hair into curls or waves to enhance aesthetic appearance. Along with the development of beauty trends, various innovations in perming techniques have emerged, one of which is double perming. This technique is carried out through two stages of hair rolling to produce curls that are more uniform, well-defined, and longer-lasting. This study aims to describe the concept, techniques, as well as the advantages and disadvantages of double perming in cosmetology. The method used is descriptive qualitative with a literature study approach, involving the review of various sources such as books, scientific journals, and related documents. The results of the study indicate that the double perming technique is effective in producing consistent wave patterns from the roots to the ends of the hair, resulting in a neater and more aesthetic appearance. This technique also facilitates further styling processes as the hair structure becomes more manageable. However, this technique has a higher level of complexity and has the potential to cause hair damage if not performed properly. Therefore, a good understanding of hair conditions, perming techniques, as well as the appropriate use of tools and materials is required.